Experimental and theoretical studies on reducing hot spot stress on CHS gap K-joints with CFRP strengthening. (15th December 2019) - Tong, Lewei; Xu, Guowen; Zhao, Xiao-Ling; Zhou, Haiming; Xu, Fei
Highlights: An effective CFRP fatigue strengthening scheme is introduced for CHS gap K-joints. Experiments are performed to measure SCFs of CHS gap K-joints before and after CFRP strengthening. Hot spot stress on CHS gap K-joint is significantly reduced by CFRP strengthening. Theoretical formulas are developed for the SCF reduction coefficient in CFRP-strengthened joints. Abstract: This paper presents an experimental investigation into reducing the hot spot stress on gap K-joints made of circular hollow sections (CHS) with carbon fibre reinforced polymer (CFRP) strengthening. A series of well-designed CHS gap K-joints were strengthened by using combinations of unidirectional and bidirectional CFRP sheets. Hot spot stress tests were conducted on the joints before and after strengthening. By comparing stress concentration factors (SCFs), it was found that the proposed CFRP strengthening scheme could effectively reduce the hot spot stress on CHS gap K-joints, thereby prolonging the fatigue life of joints. Generally, the maximum SCFs in the chord and brace decrease by an average of 20% and 15%, respectively. Furthermore, a theoretical analysis was conducted to develop formulas for the SCF reduction coefficient, which were verified by test results. SCF formulas were suggested for CFRP-strengthened CHS gap K-joints.